Application of Marketing Communication Strategy in Marketing Activities Consumer Goods Products (Case Study at PT XYZ) - Zainul Wasik; Kuncoro Catur Nugroho; Muchammad Saifuddin (Journal of Managerial Sciences and Studies, 2023)
Objective - This study aims to determine marketing communication strategies in consumer goods marketing activities at PT XYZ in Surabaya. Design/methodology/approach - The object of this research was to examine marketing communication strategies in consumer goods marketing activities at PT XYZ in Surabaya. The subject of research is PT XYZ which is located in Surabaya and the company was chosen because of its position as a market leader in the field of consumer goods product distributors. Findings - The results showed conformity between conceptual patterns predicted based on relevant theories with patterns of empirical findings of case studies. Based on the analysis carried out, it is concluded that the marketing communication strategy of PT XYZ uses a promotional mix in the form of advertising, sales promotion, personal selling, and marketing events. Marketing communication activities are widely supported by brand-holder companies or principals